PENOLAKAN TIONGKOK TERKAIT PENGAJUAN KEANGGOTAAN INDIA DALAM NUCLEAR SUPPLIERS GROUP (NSG) - Parama Nanda, I Made Widhi Sadhana; Priadarsini, Ni Wayan Rainy; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
A BS TR A C T   T h i s   research   aims   t o e x p lain   w hy   C hina   opposes   I ndia’s   m embership   i n t he   N uclear   Supplie rs Group (NSG) by using explanatory q ualitative m ethods. I ndia's d esire t o become a m e m b er o f t he N SG i s based on I ndia's f u lfillment o f c l ean energy and gaining i nternational legitimacy as nu c l ea r w eapons   c ountries.   T h e   s ubmission   o f   I ndia   m e m bership   i s   s upported   by   a   m ajority   o f   N SG m embers including f our c o untries f rom t he P 5 C ountries. Although, m any c ountries s u pported t he s ubmission   of   I ndian   m e m bership,   C h ina   decided   t o   oppose,   w hich   m ake   C hina   t h e   only   P 5 C ountries   t hat   blocks   I ndia's   m embership   i n   t h e   N SG.   T his   research   uses   t he   N e o r eali s m f r a m e w ork t o answer t h e r easons behind C hina's refusal on I ndia’s m e m b ership i n t he N SG. T he research t hen f ound t he a nswer t hat C hina's rejection w as based on C hina's e ff orts t o protect i t s s urvival f rom t h r eats f rom other c ountries w hile s imultaneously   m aintaining   a s t r ategic balance i n t he South Asian r egion.     K eywords:   C h i na,   I ndia,   N eorealism,   N uclear   Suppliers   G roup   ( N SG )